THE EXPERIMENTAL RESEARCH OF THE TECHONOLOGY OF FUTURE ATCO-TRAINERS' PEDAGOGY COMPETENCE FORMATION - Людмила Немлій (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article analyzes the experimental research of pedagogical competence formation of future air traffic control officers-trainers (ATCO-trainers). At the stage of forming experiment a course «Fundamentals of ATCOtrainer's educational activities» was developed and introduced into the process of professional training of future ATCO-trainers. According to the plan of this course, the organization of educational process was carried out based on the integrative technology. The results of the forming experiment demonstrate the effectiveness of the implemented technologies.